2012
DOI: 10.1002/jor.22132
|View full text |Cite
|
Sign up to set email alerts
|

BMP‐2 but not VEGF or PDGF in fibrin matrix supports bone healing in a delayed‐union rat model

Abstract: Treatment of delayed bone healing and non-unions after fractures, osteotomies or arthrodesis still is a relevant clinical challenge. Artificially applied growth factors can increase bone healing and progressively gain importance in clinical routine. The aim of this study was to determine the effects of rhPDGF-BB, rhVEGF-165, and rhBMP-2 in fibrin matrix on bone healing in a delayed-union rat model. Thirty-seven rats underwent a first operation where a standardized femoral critical size defect was created. A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 28 publications
2
27
0
2
Order By: Relevance
“…As a consequence osseous unions as well as narrow unions occurred in 2 out of 6 animals respectively. The results are supported by a previous study [32].…”
Section: Discussionsupporting
confidence: 91%
“…As a consequence osseous unions as well as narrow unions occurred in 2 out of 6 animals respectively. The results are supported by a previous study [32].…”
Section: Discussionsupporting
confidence: 91%
“…These effects may explain why VEGF has been found to enhance bone healing and regeneration in many studies but has failed to have positive effects in others using ex vivo VEGF gene therapy or recombinant VEGF (13,(46)(47)(48). An important conclusion from the present study is that optimal amounts of VEGF are critical for the therapeutic outcome.…”
Section: Discussionmentioning
confidence: 72%
“…Although many studies have reported a positive correlation between PDGF administration and enhanced bone healing, these observations were not shared by all. Kaipel et al (2012) demonstrated the failure of PDGF treatment to increase bone healing within a femoral segmental defect in rat. The same study also demonstrated failed healing following administration of another angiogenic factor VEGF.…”
Section: Direct Administration Of Pdgfmentioning
confidence: 99%
“…However, selection according to the task at hand, whereby combination treatment with FGF-2 may be required to induce void filling callus formation and osteoid production prior to combination treatment with BMP-2 for mineralisation. A staged approach may be necessary for efficient and effective bone healing requiring multiple growth factors delivered spatiotemporally in (Lee et al, 2001b) and rat (Kaipel et al, 2012) for bone tissue engineering strategies (Supplementary Table 4). …”
Section: Combination Administration Of Fgfmentioning
confidence: 99%